ANALISIS PENANGGULANGAN CURANMOR DI SURABAYA DITINJAU DARI KEKOSONGAN HUKUM ASPEK PREVENTIF DAN REPRESIF - Cynthia Ariestianto Wijaya (The Juris, 2026)
Motor vehicle theft crimes (curanmor) in the Surabaya region experienced a significant increase in 2025-2026, with crime patterns that are far more organized and clandestine. This research was conducted with the aim of analyzing legal gaps in addressing curanmor from both preventive and repressive aspects, as well as providing ideal formulations to strengthen the effectiveness of law enforcement in the jurisdiction of Polrestabes Surabaya. The research method used is normative juridical with a statutory approach (statute approach) and a conceptual approach (conceptual approach). The research findings indicate the existence of fundamental legal gaps, due to existing regulations (Criminal Code and Law No. 1 of 2023) being general in nature and curanmor not yet classified as an organized clandestine crime. In addition, there are normative gaps in the preventive aspect that regulate the relationship between the police and the community, which serves as the primary spearhead, by utilizing integrated monitoring technology through administrative recording of vehicle ownership in rural areas. Optimization of repressive efforts is also based on civilian informants as a bridge, equipped with techniques for purchasing stolen motorcycles. This strategy is expected to disrupt the economic chain of crime, which is the fundamental factor behind the proliferation of motor vehicle theft crimes in Surabaya.